From peak to retraction: analysing the public administration teaching stages of construction in Brazil (1966-1982) - Coelho, Fernando de Souza; Nicolini, Alexandre Mendes (Organizações & Sociedade, 2013)
The history of undergraduate education in Public Administration in Brazil unfortunatelyhave a small amount of descriptive studies and analytical investigationsof the subject, inspite of the thesis of Fischer (1984), Coelho (2006), Nicolini(2007) and few articles or research reports. The objetive of this paper is bothto propose a timeline for such education in Brazil as contributing to the descriptionand analysis of one of its cycles. Methodologically, the article reviews those worksthat directly and indirectly address the issue and analyzes the laws and opinions onundergraduate teaching in Public Administration. It also considers the pedagogical projects and discussion texts of educational institutions offering Public Administrationthis courses at that time. There have been identified three cycles of teaching in PublicAdministration: the first cycle shows the rise of undergraduate education in publicadministration between 1952 and 1965. The second cycle focuses on the peak and fallof undergraduate education in the period between 1966 and 1982, in which this paperfocuses. The third cycle shows a (re)encouragement in the area when new trainingproposals emerge in the years 1983 to 1994. The findings show the North Americaninfluence in the second cycle, the indefinition between the fields of public administrationand business administration, the impetus given to business administrators byDecreto Lei 200 and the discouragement of teaching Public Administration because ofnational curricula enforcement and reducing labor market for public administrators.